2017
DOI: 10.1007/s10529-016-2282-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel, versatile family IV carboxylesterase exhibits high stability and activity in a broad pH spectrum

Abstract: The combination of Est06 properties place it among novel biocatalysts that have potential for industrial use including low temperature applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Mechanisms involved in metal ion resistance in esterases are not well established, with different effects on enzyme activity being observed with some metal ions. For example while the Est06 esterase has been shown to be resistant to Cu 2+ (Dukunde et al, 2017), we found Cu 2+ to have a positive effect on 7N9 esterase activity as it also has on esterase activity in a cold adapted enzyme isolated from Shewanella sp. (Hang et al, 2016).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Mechanisms involved in metal ion resistance in esterases are not well established, with different effects on enzyme activity being observed with some metal ions. For example while the Est06 esterase has been shown to be resistant to Cu 2+ (Dukunde et al, 2017), we found Cu 2+ to have a positive effect on 7N9 esterase activity as it also has on esterase activity in a cold adapted enzyme isolated from Shewanella sp. (Hang et al, 2016).…”
Section: Discussionmentioning
confidence: 60%
“…Interestingly a novel carboxylesterase Est06, isolated from a forest soil metagenomics library has also recently been reported to share 61% similarity with a hypothetical protein from Candidatus Entotheonella sp. TSY1 (Dukunde et al, 2017). FIGURE 7 | pH dependency of 7N9 esterase.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many bHSL genes were identified through metagenomic approaches directly from environmental DNA samples [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]. These metagenomic bHSLs were isolated from soil [46,53,55,56], mud and sediment-rich water [47], environmental soils [48], forest soil [49,60,64], marine sediments [50,51,58], activated sludge [52,54], mountain soil [57], tidal flat sediment [59], surface sediment [61], and permafrost [62,63]. Interestingly, bHSL family members were shown to be selectively inhibited by 5-methoxy-3-(4-phenoxyphenyl)-3H- [1,3,4]oxadiazol-2-one [65].…”
Section: Bacterial Hormone-sensitive Lipasesmentioning
confidence: 99%
“…Similarity searches showed that protein sequences similar to Est56 were mainly identified during metagenome screenings. These comprised ELP45 isolated from a forest topsoil [66], EstC23 from mountain soil [67], Est06 from forest soil [68], and EstMY from activated sludge [69], which showed 62%, 61%, 60%, and 60% amino acid identity to Est56, respectively.…”
Section: Identification and Sequence Analysis Of A Novel Lipolytic Genementioning
confidence: 99%